2022
DOI: 10.3389/fncir.2021.815554
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Selective Response Plasticity in Primary Visual Cortex: Progress and Puzzles

Abstract: Stimulus-selective response plasticity (SRP) is a robust and lasting modification of primary visual cortex (V1) that occurs in response to exposure to novel visual stimuli. It is readily observed as a pronounced increase in the magnitude of visual evoked potentials (VEPs) recorded in response to phase-reversing grating stimuli in neocortical layer 4. The expression of SRP at the individual neuron level is equally robust, but the qualities vary depending on the neuronal type and how activity is measured. This f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 152 publications
(282 reference statements)
0
23
2
Order By: Relevance
“…Many related studies have shown evidence for cortical novelty responses across brain regions, with wide variation in the effort to control for adaptation ( Kato et al, 2015 ; Makino and Komiyama, 2015 ; Garrett et al, 2020 ; Poort et al, 2021 ; Schulz et al, 2021 ; Homann et al, 2022 ; Montgomery et al, 2022 ). In most cases, consistent with efficient coding, novel stimuli evoke more spiking activity than familiar.…”
Section: Efficient Coding In Primary Visual Cortexmentioning
confidence: 99%
“…Many related studies have shown evidence for cortical novelty responses across brain regions, with wide variation in the effort to control for adaptation ( Kato et al, 2015 ; Makino and Komiyama, 2015 ; Garrett et al, 2020 ; Poort et al, 2021 ; Schulz et al, 2021 ; Homann et al, 2022 ; Montgomery et al, 2022 ). In most cases, consistent with efficient coding, novel stimuli evoke more spiking activity than familiar.…”
Section: Efficient Coding In Primary Visual Cortexmentioning
confidence: 99%
“…Despite abundant evidence supporting the hypothesis that potentiation of thalamocortical synapses is the molecular basis for SRP (Frenkel et al, 2006;Cooke and Bear, 2010), it is now very clear that this does not occur on excitatory neurons in L4 (Montgomery et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Despite abundant evidence supporting the hypothesis that potentiation of thalamocortical synapses is the molecular basis for SRP (Frenkel et al, 2006; Cooke and Bear, 2010), it is now very clear that this does not occur on excitatory neurons in L4 (Montgomery et al, 2021). Indeed, recent findings indicate that SRP expressed as VEP potentiation in L4 is most parsimoniously explained by an experience-dependent reduction in inhibition mediated by PV+ interneurons in this layer (Kaplan et al, 2016; Hayden et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, in wild-type mice, chronic deprivation initiated at eye opening significantly decreased the strength of deprived-eye visual responses and affected orientation and direction selectivity, these changes did not occur in MMP9 −/− mice raised with conventional binocular vision. However, MMP9 −/− mice turned out to be insensitive to visual cortex plasticity in response to chronic deprivation, while they appeared totally normal when considering other forms of experience-dependent plasticity, such as the well-established mechanism of stimulus-selective response potentiation [ 12 ]. These results will help to expand the knowledge concerning the molecular specificity of distinct forms of activity-dependent plasticity in the mouse visual system.…”
mentioning
confidence: 99%